Statute of limitations - Havill, Steven; Brush, Stephanie (Spokane, WA Books in Motion, 2006)
It's Christmas in Posadas County, and Undersheriff Estelle Reyes-Guzman is settling down to a quiet evening with her family and friend ex-Sheriff Bill Gastner, that is until her doctor husband gets a disturbing call. Retired chief-of-police Eduardo Martinez is calling from a nearby motel where he is having chest pains. Not nine minutes later Estelle gets a call that there has been an incident at the same motel. Estelle and ex-Sheriff Bill Gastner, arrive at the motel parking lot to find it has turned into a crime scene, and the body of the retired chief-of-police is at the center. It appears that Eduardo had an exchange with two men and then collapsed while the men took off in his car. An out-of-town couple are the only witnesses, but their story doesn't ring true.
Unabridged.
Compact discs.
Read by Stephanie Brush.
105216
Keywords: Reyes-Guzman, Estelle (Fictitious character) -- Fiction; Gastner, Bill (Fictitious character) -- Fiction; Reyes-Guzman, Estelle (Fictitious character) -- Fiction; Sheriffs -- Fiction; New Mexico -- Fiction; Audiobooks; Fiction; Mystery fiction